Clinical Implication of Highly Sensitive Detection of the BRAFV600E Mutation in Fine-Needle Aspirations According to the Thyroid Bethesda System in Patients With Conventional Papillary Thyroid Carcinoma. (May 2015) - Seo, Jae Young; Choi, Jong Rak; Moon, Hee Jung; Kim, Eun-Kyung; Han, Kyung Hwa; Kim, Hyunki; Kwak, Jin Young
Background: We investigated the additional diagnostic yield of the mutation test and evaluated the frequency of the BRAF mutation in conventional PTC (cPTC) according to ultrasound (US) features and the Bethesda System for Reporting Thyroid Cytopathology (BSRTC) based on the BRAF V600E mutation status. Materials and Methods: During the study period, 279 patients who underwent FNA with an additional BRAF V600E mutation test were diagnosed as cPTC after surgery. We analyzed the association between the mutation and several clinical factors. Results: Of the 279 cPTCs, 250 (89.6%) had the BRAF V600E mutation. The BRAF mutation test was helpful in diagnosing an additional 19% (53/279) of cPTCs. The frequency of the BRAF mutation in cPTCs with suspicious US features was higher than that of cPTCs with negative US features regardless of the BSRTC. Conclusions: Suspicious US features may be helpful in deciding whether an additional BRAF V600E mutation test should be done in thyroid nodules with indeterminate cytology.